Pengaruh Edukasi Gizi melalui Media Video terhadap Pengetahuan Remaja tentang Gizi Seimbang di SMA Negeri 7 Batang Hari - Khairunnisa, Yulia; Jeki, Andicha Gustra; Wulansari, Arnati; Indrawati, Iin (Universitas Baiturrahim, 2025)
One effort to improve knowledge is through nutrition education using video media. Video media is expected to stimulate the senses of hearing and sight during the delivery of educational material. The purpose of this study was to determine the effect of using video media on the level of balanced nutrition knowledge among adolescents at SMA N 7 Batang Hari. This study was conducted in July 2024 at SMA N 7 Batang Hari using educational video media. This study used a One Group Pretest–Posttest Design. The sample size was 30 people. The sampling technique used was purposive sampling. The intervention provided was education about balanced nutrition using educational video media. Knowledge data was based on the scores obtained. Data analysis used the Wilcoxon test. The results showed an increase in knowledge and indicated that nutrition education using videos had an effect on improving adolescents knowledge. It is recommended that respondents understand and study the videos presented by the researchers and review the material provided by the researchers.